2021
DOI: 10.1186/s12986-021-00546-3
|View full text |Cite
|
Sign up to set email alerts
|

The relation between low carbohydrate diet score and psychological disorders among Iranian adults

Abstract: Background Since evidence regarding to low carbohydrate diet (LCD) and psychiatric disorders is little and controversial, this study aimed to assess relation between LCD score and psychological disorders including depression, anxiety, and stress among a large representative sample of Iranian adult population in Yazd city, Iran. Methods This cross-sectional analysis was conducted on data of 7165 persons who participated in the recruitment phase of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Dietary pattern assessment takes both the complexity and synergistic effect of the foods and nutrients that make up a diet into account (11)(12)(13) . Low-carbohydrate diet (LCD) is a diet with lower intakes of carbohydrate and higher consumption of fat and protein (9,10,14) . Studies suggest that higher carbohydrate intake is followed by lower HDL, hypertriglyceridemia and hyperinsulinemia (4,15,16) .…”
mentioning
confidence: 99%
“…Dietary pattern assessment takes both the complexity and synergistic effect of the foods and nutrients that make up a diet into account (11)(12)(13) . Low-carbohydrate diet (LCD) is a diet with lower intakes of carbohydrate and higher consumption of fat and protein (9,10,14) . Studies suggest that higher carbohydrate intake is followed by lower HDL, hypertriglyceridemia and hyperinsulinemia (4,15,16) .…”
mentioning
confidence: 99%
“…Prospective studies have reported that dietary patterns characterized by high intake of protein and fat and low intake of carbohydrate were associated with lower risks of cognitive impairment and dementia [ 68 , 69 ]. Some other studies have reported that a low-carbohydrate diet was associated with lower risks of depression in Iranian women [ 70 ] and patients with diabetes [ 71 ]. Moreover, we propose that another possible reason for this association may be that individuals with a high consumption of staples foods have a lower score for DDS in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, score ranged from 0 (the highest carbohydrate intake and the lowest fat and protein intakes) to 30 (the highest protein and fat intakes and the lowest carbohydrate intake) [29]. Therefore, participants with higher score adherence to a low-carbohydrate diet [30].…”
Section: Calculation Of the Low-carbohydrate-diet Scorementioning
confidence: 99%